Gender-based discrimination and son preference in Punjabi-Canadian families: a community-based participatory qualitative research study - Cindy-Lee Dennis; Susitha Wanigaratne; Marcelo Urquia; Pamela Uppal; Alia Januwalla; Amanpreet Brar; Manvir Bhangu; Amrita Kumar-Ratta (BMJ Open)
Objectives To conduct a qualitative study, guided by the principles of community-based participatory research, with the following objectives: (1) to provide a conceptual framework describing the drivers of son preference; (2) to understand experiences of son preference among Punjabi-Canadians and (3) with this understanding, identify and co-design an appropriate educational tool.Design, setting, participants, methods Qualitative study consisting of four bilingual (Punjabi and English) focus group discussions with 11 mothers, 4 fathers and 17 grandmothers in Toronto and Brampton, Canada. Participants were queried about experiences and perspectives related to reproductive decision-making, gender equity and son preference, and for appropriate approaches to reducing inequities. Transcripts were simultaneously translated and written in English and thematic analysis was conducted. An infoposter was identified as a feasible educational tool and was co-designed by researchers and community partners.Results Participants identified patrilocality (ie, married sons reside with parents, married daughters with in-laws) and patrilineality (ie, sons inherit assets, daughters’ husband receives a dowry) as structural precursors to proximal drivers (ie, old-age security) of son preference. Mothers’ and grandmothers’ value to their families depended strongly on having a son but did not guarantee security. Pressures (ie, internalised discrimination, reproductive coercion) to conceive a son were common after the birth of at least one daughter in the absence of sons. Participants did not know anyone who had a sex selective abortion in Canada; however, traditional sex selection methods (eg, herbal medicines) were mentioned. Our co-designed infoposter entitled ‘Truths About Son Preference’ addressed three misconceptions identified in discussions.Conclusion This study may be useful to health and social care providers in providing structurally competent and culturally humble counselling and care, particularly after the birth of daughters in the absence of sons. Community engagement is necessary for future intervention development.